2004
DOI: 10.1267/ahc.37.139
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Hepatocyte Growth Factor and Its Specific Receptor c-Met Expression in Colorectal Cancer Progression

Abstract: To clarify the clinical significance of hepatocyte growth factor (HGF) and its specific receptor c-Met in colorectal cancer, we performed serological analysis of HGF in 108 patients who underwent colon cancer surgery and 200 agematched control subjects, and immunohistochemical analysis of HGF and c-Met in surgically resected samples in 50 of the 108 patients. Serological analysis demonstrated that preoperative serum HGF level was significantly higher in the cancer group than in the control group (p<0.0001), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Three fields of each section were observed at 200× magnification using a BHS/System Living microscope (Olympus Corp., Tokyo, Japan) and the results were classified as positive when the ratio of stained cancer cells was >25%, according to previous studies that were analyzed for comparison ( Fig. 1 ) ( 8 , 29 – 31 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three fields of each section were observed at 200× magnification using a BHS/System Living microscope (Olympus Corp., Tokyo, Japan) and the results were classified as positive when the ratio of stained cancer cells was >25%, according to previous studies that were analyzed for comparison ( Fig. 1 ) ( 8 , 29 – 31 ).…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study by our group, an association between elevated pre-operative serum HGF levels and advanced disease stages in colon cancer was identified, mainly regarding the depth of tumor invasion into the wall and liver metastasis, which suggested the expression of the HGF/c-Met pathway as a potential predictive factor of colon cancer progression ( 8 ). In the present study, serological and immunohistological analyses were conducted in order to evaluate the clinical significance of the expression of the HGF/c-Met pathway in assessing the stage of gastric cancer progression.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Investigating the relationship between CRC and HGF and mesenchymal epithelial transition factor (c-Met), we found higher preoperative levels of expression of circulating HGF/c-Met in patients with hepatic metastases. The results of the immune staining were, however, unpredicted, demonstrating increased expression of HGF and decreased expression of c-Met as disease staging progressed (6). Our present understanding of this phenomenon suggests that the production of HGF by both paracrine and endocrine mechanisms leads to the supersaturation and downregulation of c-Met (6).…”
Section: Relationship Between Serum and Urinary Fn Levels In Patientsmentioning
confidence: 82%
“…The results of the immune staining were, however, unpredicted, demonstrating increased expression of HGF and decreased expression of c-Met as disease staging progressed (6). Our present understanding of this phenomenon suggests that the production of HGF by both paracrine and endocrine mechanisms leads to the supersaturation and downregulation of c-Met (6). In another study, we found that TGF-ß1 expression within CRC tissue was significantly higher in patients with lymphatic metastases and high-grade venous infiltration, and that serum TGF-ß1 levels were also significantly higher in patients with CRC than in the controls.…”
Section: Relationship Between Serum and Urinary Fn Levels In Patientsmentioning
confidence: 99%